Studies on the Sterol of Bombyx mori L. II. Quantitative Analysis of Total Sterol in the Silkworm - Tsuda, Kyosuke; Akaike, Eiko; Ikekawa, Nobuo; Suzuki, Mieko (Chemical & pharmaceutical bulletin, 1966)
The quantitative analysis of sterols in the silkworm was carried out by means of gas chromatographic technique . The amount of sterol in whole body was 0.59mg. and sterol percentage of live weight was 0.066%, as an average, showing that sterol percentage in unfeeding silkworm was larger than that in feeding larva. Furthermore sterol percentage (0.024%) of blood in the silkworm was lower than that in mammals. The amount of cholesterol calculated from total sterol in the whole body was larger than threshold amount of brain hormone cholesterol in the silkworm for the induction of imaginal development On the other hand, the critical period of the brain hormone for the development was coincided with time of sudden increase of blood sterol.